Transaction Analysis of Academic EBook Usage: The Case of Ebrary - Pervaiz Ahmed,Mark Brogan (IJoLIS, 2024)
Purpose: This paper Explored The Patterns (way and extent) of e-book use in an Australian case study academic and research library.